Evaluation of the Cookies Formulated with Costus igneus Plant Material for Antidiabetic Activity (Medico Legal Update, 2020)
Diabetes Mellitus is a fast-growing disorder in the current scenario commonly affecting all age groupsespecially elder groups. The high blood glucose can be kept in control with nutraceutical foods. The presentstudy is aimed to formulate a nutritionally rich cookie with Costus igneus leaf extract and to determine theeffect of cookie consumption on decreasing blood glucose levels in type 2 diabetic patients. Cookies madewith Costus igneus leaf powder etc. were analyzed for proximate analysis and phytochemical analysis withstandard procedures. A total of 30 Type-II diabetic patients were selected for the study whose demographicvariables and blood glucose levels were measured on the first day and after 15 days, 30 days of cookiesconsumption. The proximate and physic-chemical analysis showed cookies contain high amount of secondarymetabolites including antioxidant compounds. Among the 30 study subjects, the mean levels of FBS andPBS were decreased significantly in all the four groups from day 0 to day 30 which indicates that C.igneus cookies consumption had good effect in reducing the blood glucose levels. However the HbA1C has beendecreased by one unit in all the four study groups. The cookies made with Costus igneus plant material havegood antimicrobial, antioxidant and antidiabetic activities and can be used as a therapeutic and functionalfood source for the treatment of overweight, obesity and diabetes.